Peningkatan Hasil Belajar Keliling dan Luas Bangun Datar Menggunakan Model Discovery Learning di Kelas V SDN 15 Padang Sarai - Dwiyano Putri, Rivo; Masniladevi, Masniladevi; Ahmad, Syafri; Helsa, Yullys (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This researcher aims to describe the improvement in learning outcomes for the circumference and area of ​​flat shapes using the Discovery Learning model in class V of SDN 15 Padang Sarai Koto Tangah. This research is a classroom action research (CAR) with a qualitative and quantitative approach carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle has four stages of research, namely planning, implementation, observation and reflection. Data collection techniques include interviews, observations, tests, and non-tests. The subjects of this study were teachers and students in class V of SDN 15 Padang Sarai Koto Tangah with a total of 26 students. The results of the study showed that there was an increase in three aspects of the study, namely: a) Cycle I Teaching Module with an average of 84.49% (good) increasing in cycle II to 96.42% (very good); b) Implementation of teacher aspects in cycle I with an average of 90.62% (good) increasing in cycle II to 96.87% (very good); and c) Assessment of student learning outcomes in cycle I with an average of 90.62% (good) increasing in cycle II to 96.87% (very good). Based on the results of the study, it can be concluded that the use of the discovery learning model can improve student learning outcomes in learning about the circumference and area of ​​flat shapes.